(untitled) (Journal of actual problems of jurisprudence, 2019)
In this article, the authors examined the issue of the application of compulsory medical measures to the insane. The use of compulsory medical measures in relation to the insane is a complex procedural act, since this section of the criminal procedure code considers the rights and legitimate interests of the insane person. In this article, the authors, having investigated the world and native opinions concerning this problem, try to give their own opinion on this problem. Also, the authors investigated and disclosed the features of the application of compulsory medical measures to the insane. The decision of the court on forced outpatient monitoring and psychiatric treatment is not only announced to the person, but also the court decision must be sent to the justice authorities, as well as to psycho-neurological clinics. The convicted is examined by a doctor at intervals determined by the psychiatrist. The person performs the diagnostic and therapeutic measures suggested by the psychiatrist. If the punishment is not related to imprisonment, social assistance will be provided to the person in the process of comprehensive medical and social rehabilitation. In the case of an increased risk of mental disorders of a person, the court may forcibly conduct compulsory outpatient treatment in a psychiatric clinic (usually, on the recommendation of the Commission, in a general hospital). The purpose of this article is, based on the theoretical and practical knowledge already accumulated in this field, as well as the norms of the current Code of Criminal Procedure, to investigate the problem, and on its basis to work out proposals for improving the criminal procedure legislation and law enforcement practice. The relevance of the research topic is due to the fact that, in the science of the criminal process the main thing is to ensure the right to defense of the suspect, the accused and the defendant, as well as to ensure the efficiency and economy of the criminal process. Based on the study, the authors attempted to analyze the application of coercive measures of a medical nature to the insane in native and international practices. Key words: compulsory medical measures, accused, guilt, criminal process, insane.